Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00268-016-3656-1
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Intraoperative Porto‐Caval Shunts in Piggy‐Back Liver Transplantation Reduce Intraoperative Blood Loss and Improve Postoperative Transaminases and Renal Function: A Meta‐Analysis

Abstract: This meta-analysis found that temporary intraoperative porto-caval shunts in cava-sparing liver transplantation reduce blood loss as well as hepatic injury and enhance postoperative renal function without prolonging operative time. Randomized controlled trials investigating the use of temporary intraoperative porto-caval shunts are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
2
14

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 36 publications
0
21
2
14
Order By: Relevance
“… Content is partially adopted from the meta‐analysis by Pratschke et al (↑) = significant more, (↓) = significant less, (=) = no significant difference. …”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“… Content is partially adopted from the meta‐analysis by Pratschke et al (↑) = significant more, (↓) = significant less, (=) = no significant difference. …”
Section: Discussioncontrasting
confidence: 58%
“…These studies do not describe the order of reperfusion used during transplantation, although we assume that portal reperfusion was first. A meta‐analysis performed by Pratschke et al showed a significant beneficial effect of a TPCS on operative blood loss, but the I 2 values indicated substantial heterogeneity among the studies ( P < 0.05), which could bring a potential bias to the results …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique preserves caval flow during the whole procedure and therefore reduces hemodynamic instability and the corresponding negative effect on renal function. In cases where closure of the portal vein is poorly tolerated, especially in patients with metabolic disease or acute liver failure who lack portosystemic collaterals, a temporary portocaval shunt can be constructed 98,99 , and many centers use this as standard technique in LT.…”
Section: Surgical Techniquementioning
confidence: 99%